A Comparative Investigation of Chemical Decontamination Methods for In-Situ Cleaning of Dental Implant Surfaces - Badra Hussain; Sadia Khan; Anne Eriksson Agger; Jan Eirik Ellingsen; Ståle Petter Lyngstadaas; Jaime Bueno; Håvard J. Haugen (Journal of Functional Biomaterials, 2023)
Surface chemistry evaluation is crucial in assessing the efficacy of chemical decontamination products for titanium implants. This study aimed to investigate the effectiveness of chemical decontamination solutions in cleaning a contaminated dental implant surface and to evaluate the potential of combining Pluronic gel with hydrogen peroxide (NuBone®Clean) by evaluating pellicle disruption and re-formation on implant surfaces. In addition, ensuring safety with in vitro and human testing protocols. X-ray Photoelectron Spectroscopy (XPS) was utilised for surface analysis. All the tested gels had some effect on the surface cleanness except for PrefGel®. Among the tested chemical decontamination candidates, NuBone®Clean demonstrated effectiveness in providing a cleaner titanium surface. Furthermore, none of the tested chemical agents exhibited cytotoxic effects, and the safety assessment showed no adverse events. The results of this study highlight the significance of conducting comprehensive evaluations, encompassing safety and efficacy, before introducing new chemical agents for dental treatments. The findings suggest that NuBone®Clean shows potential as a chemical decontamination solution for implant surfaces. However, further investigation through randomised clinical trials is necessary. By adhering to rigorous testing protocols, the development of safe and efficient chemical decontamination strategies can be advanced, benefiting patients and promoting progress in implant dentistry.